2017
DOI: 10.3390/w9010057
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TRMM Product for Monitoring Drought in the Kelantan River Basin, Malaysia

Abstract: Assessment of satellite precipitation products' capability for monitoring drought is relatively new in tropical regions. The purpose of this paper is to evaluate the reliability of the Tropical Rainfall Measuring Mission (TRMM) Multisatellite Precipitation Analysis (TMPA) 3B43 product in estimating the standardized precipitation index (SPI) in the Kelantan River Basin, Malaysia from 1998 to 2014, by comparing it with data from 42 rain gauges. Overall, the TMPA-3B43 performed well in the monthly precipitation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 52 publications
2
37
1
1
Order By: Relevance
“…Similar results were reported in the study of Cai et al [19] and Xue et al [64], where the mountainous areas show better correlation between 3B42V7 and the rain gauge data. However, the finding is inconsistent with the study by Tan et al [14] in the Kelantan River Basin, Malaysia, where lower CC values are found over the mountainous regions in the southwestern part of the basin. The reason for this difference is related to the different geographical location and magnitude of precipitation in different study area.…”
Section: Overall Assessmentcontrasting
confidence: 96%
See 2 more Smart Citations
“…Similar results were reported in the study of Cai et al [19] and Xue et al [64], where the mountainous areas show better correlation between 3B42V7 and the rain gauge data. However, the finding is inconsistent with the study by Tan et al [14] in the Kelantan River Basin, Malaysia, where lower CC values are found over the mountainous regions in the southwestern part of the basin. The reason for this difference is related to the different geographical location and magnitude of precipitation in different study area.…”
Section: Overall Assessmentcontrasting
confidence: 96%
“…As we all know, The TRMM was originally launched to measure the intensity and area coverage of rainfall around the tropical and semi-tropical areas, as the latitude increases, the detection capability gradually decreases. In addition, the TRMM sensors have better detection capability on the heavy precipitation cloud system [14,62], while over 90% of the precipitation in the Hexi region is concentrated in the warm season, and the heavy precipitation events are all concentrated in this period. In contrast, the poor performance of TRMM 3B42V7 during the cold season can be attributed to the poor detection capability of the light precipitation (less than 3 mm/day) [63].…”
Section: Overall Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of existing hydrological and climatological studies, including analyses of the impacts of extreme climatic events have been conducted using ground-based gauge data [7,61]. Therefore, evaluation of other types of precipitation products for extreme events would provide important insight for determining their efficacy and accuracy for unusual climatic conditions [62]. Four indices were used in this study to assess the performance of the three GCPs in capturing the pattern of precipitation extremes over the KRB and JRB: (1) the number of precipitation days ≥10 mm·day −1 in a year (R10mm); (2) the number of precipitation days ≥50 mm·day −1 in a year (R50mm); (3) the annual maximum daily precipitation/streamflow amount(Rx1d); and (4) the annual maximum consecutive five-day precipitation/streamflow amount (Rx5d).…”
Section: Extreme Events Analysismentioning
confidence: 99%
“…Hydrologic studies play a major role in the monitoring of natural hazards such as droughts [2] and floods [3][4][5]. The most important variable for hydrologic applications is the accurate spatial rainfall data [6], which is a critical input for hydrologic models [3,4,7].…”
Section: Introductionmentioning
confidence: 99%